Penatalaksanaan Mucocele Dengan Teknik Eksisi Menggunakan Anestesi Umum - Meitty Caesarini; Machmud Al Husaerry; Iwan Ahmad Musnamirwan (Riviera Publishing, 2025)
Mucocele is a benign lesion commonly found in the oral cavity, particularly on the lower lip, resulting from mucus retention or extravasation from the minor salivary glands. Although typically painless, it can interfere with oral functions such as speaking and eating, affecting patient comfort. Surgical excision is the preferred management, especially for large, recurrent, or functionally disruptive lesions. This case report presents the management of a mucocele in a pediatric patient using an excision technique under general anesthesia, considering the patient’s young age, limited cooperation, and the sensitive location of the lesion. The procedure was performed carefully to avoid damage to adjacent tissues and minimize recurrence risk. The outcome showed good healing without complications and a significant improvement in the patient's comfort. Excision under general anesthesia is an effective management option for mucocele in pediatric cases where conventional approaches are challenging.